Selective α7 nicotinic receptor agonists and positive allosteric modulators for the treatment of schizophrenia – a review. (2nd June 2020) - Antonio-Tolentino, Kirsten; Hopkins, Corey R.
ABSTRACT: Introduction: Alpha 7 nicotinic acetylcholine receptor (α7 nAChR) partial agonists, agonists, and positive allosteric modulators (PAMs) have been in development for over a decade. The initial candidates were in clinical trials for a wide variety of diseases including schizophrenia, but there has yet to be a successful compound to make it to the market for any disorder. Although difficult to assess the cause of all the clinical failures, the lack of efficacy played a major role. The development of more selective compounds, may bring a successful compound to long-suffering schizophrenia patients. Areas covered: This article examines investigational agonists and positive allosteric modulators of the α7 nicotinic receptor in preclinical studies as well as clinical trials. Our search included the use of SciFinder, Google, and clinicaltrials.gov with search dates of 2015 to the present. Expert opinion: Researchers must rethink their approach should look more closely at the selectivity of new compounds and how to tackle the translational gap. Perhaps new positive allosteric modulators that can help minimize receptor desensitization and selectivity profiles can be a path forward for α7 nAChRs in schizophrenia.